Inotropic Effects of Prostacyclins on the Right Ventricle Are Abolished in Isolated Rat Hearts With Right-Ventricular Hypertrophy and Failure. Issue 1 (January 2017) - Holmboe, Sarah; Andersen, Asger; Johnsen, Jacob; Nielsen, Jan Møller; Nørregaard, Rikke; Bøtker, Hans Erik; Clapp, Lucie H.; Nielsen-Kudsk, Jens Erik
Abstract : Background: Prostacyclin mimetics are vasodilatory agents used in the treatment of pulmonary arterial hypertension. The direct effects of prostanoids on right-ventricular (RV) function are unknown. We aimed to investigate the direct effects of prostacyclin mimetics on RV function in hearts with and without RV hypertrophy and failure. Methods: Wistar rats were subjected to pulmonary trunk banding to induce compensated RV hypertrophy (n = 32) or manifest RV failure (n = 32). Rats without banding served as healthy controls (n = 30). The hearts were excised and perfused in a Langendorff system and subjected to iloprost, treprostinil, epoprostenol, or MRE-269 in increasing concentrations. The effect on RV function was evaluated using a balloon-tipped catheter inserted into the right ventricle. Results: In control hearts, iloprost, treprostinil, and MRE-269 improved RV function. The effect was, however, absent in hearts with RV hypertrophy and failure. Treprostinil and MRE-269 even impaired RV function in hearts with manifest RV failure. Conclusions: Iloprost, treprostinil, and MRE-269 improved RV function in the healthy rat heart. RV hypertrophy abolished the positive inotropic effect, and in the failing right ventricle, MRE-269 and treprostinil impaired RV function. This may be related to changes in prostanoid receptor expression and reduced coronary flow reserve in the hypertrophic and failing right ventricle. Abstract : Supplemental Digital Content is Available in the Text.